A Capacity Building Organisasi Pemberdayaan Kesejahteraan Sosial (PKK) Desa Ilangata Kecamatan Anggrek Kabupaten Gorontalo Utara: Capacity Building Organisasi Pemberdayaan Kesejahteraan Sosial (PKK) Desa Ilangata Kecamatan Anggrek Kabupaten Gorontalo Utara - Rizki Ayundari Putri; Fadel Ilato; Detyo Eka Cahya Salim (Madani: Jurnal Pengabdian Ilmiah, 2023)
The Family Welfare Empowerment Program (PKK) is essential as a community organization to empower women to participate in village development. In this case, women are also involved in a particular organization and can participate in village development by encouraging the participation of village communities. The method of implementing community service that is carried out is the Community Organization / Community Development (CO / CD) Method. The Community Organization / Community Development (CO / CD) method is one of the methods in social work practice with the main focus being the wider community or community with activities that involve the community to increase the level of social functioning of the community, especially in community self-involvement of Family Welfare Empowerment Program (PKK) organizations in Ilangata Village. The techniques implemented in this community service activity are observation, interviews, and Methodology Participatory Assessment (MPA). The stages of implementing this community service activity are social initiation, social organizing, social assessment, social intervention planning, and social intervention. The result of community service activities that have been carried out is the implementation of capacity-building activities for the Ilangata Village Family Welfare Empowerment (PKK) organization, which consists of reactivating organizations supported by the Decree of the Head of Ilangata Village concerning the Establishment and Appointment of the Ilangata Village Family Welfare Empowerment (PKK) Management Number 41 of 2022, capacity building resources through the provision of entrepreneurship materials and training for members of the Ilangata Village Family Welfare Empowerment Program (PKK) organization. Keywords: Capacity Building; Organization; Empowerment; Family Welfare.